(untitled) (Heritage, 2020)
In this paper the author shows the results of the research of everydayness of the Serbs in Northern Kosovska Mitrovica in the conditions of the altered socio-political context after the war on Kosovo and Metohija in 1999. The main attention was paid to the one of the fields of everyday life of Serbs in this town, and this was status and functioning of institutions. The aim of the paper was attempt to provide a contribution of the ethnographic material conceptualization based on field work in order to take into account the everyday experiences of Serbs in Northern Kosovska Mitrovica in the conditions of the undefined institutional relations caused by the withdrawal of Serbian authorities from Kosovo and Metohija, the introduction of an international protectorate and the unilateral declaration of Kosovo independence. The results presented in this paper were obtained from the field research conducted several times from 2011 to 2015 in the total duration of over eight months. The change of social-political context after the war in 1999 led to major structural disruptions in Kosovo and Metohija. These disruptions were felt especially in the institutional sphere, where their reflection came to light in almost all fields of the everyday reality of Serbs in this area. The issue of institutions, in this regard, has shown to be one of the key issues in the context of the everyday life of the Serb population in Northern Kosovska Mitrovica. The survival of the Serbian institutions for the Serbs in this town was a confirmation of the presence of the Republic of Serbia in the north of Kosovo and Metohija, according to what they figured as an important symbol of identification of the local Serbs with the state they considered their own. These institutions, on the other hand, have been under intense international and Albanian pressure since the war in 1999, which meant under the constant threat of abolition, what caused the Serbs in Northern Kosovska Mitrovica suffered a persistent sense of insecurity and concern for their own survival.